Definitions and spatialities -slum neighborhood, parish, district and suburb- and related terms. Recife: the central districts and the ‘Conjunto Urbano de Casa Forte’ - Leao Barros, Sandra (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2012)
The districts are just lines on paper. However, the lines are full of meaning, they have in the physicalgeographical support many shades of socio-economic, historical and cultural, that make them unique. Moreover, these two sets of neighborhoods that are case studies of Recife in this research, even merge with the essence of the city, a sense of identity not only to complementarity and solidarity. Limits in the abstract, concrete in another, whose analysis is beyond the scope and much of the argument of a thesis will always be on the agenda of the current urban planning, the district first and foremost is the scale of everyday life, recognizing people for living spaces. The definition of neighborhoods and the issues that define it are the focus of this research.